Dumplin' - Murphy, Julie, 1985- (Balzer + Bray, an imprint of HarperCollins Publishers, 2015)
Sixteen-year-old Willowdean wants to prove to everyone in her small Texas town that she is more than just a fat girl, so, while grappling with her feelings for a co-worker who is clearly attracted to her, Will and some other misfits prepare to compete in the beauty pageant her mother runs.